Hubungan Strategi Coping dan Work Life Balance Pada Guru Wanita di SMAN 1 Bantul - Latifa Alfiatul Fitria; Annisa Warastri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The goal of this study is to determine how coping mechanisms and work-life balance relate to one another among female instructors at SMAN 1 Bantul. A quantitative approach was taken in this investigation. Data based on the Likert Scale is gathered using the psychological scale. The study focuses on female instructors at SMAN 1 Bantul. The quantitative descriptive statistical method used in the data analysis technique necessitates that the results of data processing be presented as numerical values. The results of the hypothesis test showed a negative correlation between coping strategies and work-life balance among female teachers at SMAN 1 Bantul, with a correlation value of 0.749 and a significance level of 0.000 (p < 0.05). This means that as coping strategies increase, so does the teachers' ability to balance work and life.